PERCERAIAN NIKAH DI BAWAH UMUR DAN PENGARUHNYA TERHADAP PENGASUHAN ANAK DI KECAMATAN MANDUAMMAS KABUPATEN TAPANULI TENGAH - Abu Bakar, Erni Yanti Tinambunan, (Fakultas Agama Islam, 2022)
The age of marriage in Indonesia has been regulated by law, precisely in Article 7 paragraph 1 of Law Number 1 of 1974 which reads,